Development and characterization of an atmospheric pressure plasma reactor compatible with spatial ALD. (May 2019) - Zoubian, F; Rabat, H; Aubry, O; Dumuis, N; Dozias, S; Muñozrojas, D; Hong, D
Abstract: Dielectric Barrier Discharges (DBD) are widely used for atmospheric pressure plasma generation. The possibility of their adaptation in custom-made configurations makes them potential candidate to assist deposition processes. In fact, the increased need of high-quality thin films forces to improve the deposition techniques. New processes should be able to work in less constrained conditions such as atmospheric pressure rather than vacuum and to have faster deposition rates while respecting the same high quality of the deposited films. In this paper we present the development of a surface dielectric barrier discharge plasma reactor to assist an atmospheric spatial atomic layer deposition process. The reactor was fabricated with 3D printing and the plasma was generated by a surface dielectric barrier discharge powered by a microsecond pulsed high voltage power supply. The dissipated power was measured for different configurations, and thanks to the micro discharges imaging, it was observed that the thickness and the shape of the dielectric barrier influenced the micro discharges distribution on the dielectric surface. The plasma reactor exhaust gas was chemically analyzed by FTIR spectroscopy and micro gas chromatography. The ozone concentration was determined as function of frequency of the power supply.